Disseminated Kaposi sarcoma following COVID-19 in a 61-year-old Albanian immunocompetent man: a case report and review of the literature - Gardini, Giulia; Odolini, Silvia; Moioli, Giovanni; Papalia, Dorothea Angela; Ferrari, Vittorio; Matteelli, Alberto; Caligaris, Silvio (European journal of medical research, 2021)
Background COVID-19 and its related anti-inflammatory treatment (steroids, immunomodulators) may induce the reactivation of latent bacterial, parasitic, and viral infections. According to our knowledge, no case of disseminated HHV-8-related Kaposi sarcoma (KS) after COVID-19 and its treatment has been described so far. Only one case of cutaneous KS concurrently with COVID-19 has been previously reported. Case presentation We describe a case of disseminated KS in a 61-year-old immunocompetent Albanian man after hospitalization for COVID-19. Methods for literature research We used PubMed as biomedical database for the literature research. We selected keyword combinations including “Kaposi sarcoma,” “HHV-8,” “immunocompetent,” “COVID-19,” “SARS-CoV-2,” and “steroids.” No time or language limitation was set. Titles and abstracts of selected articles were systematically screened. Articles were included in the examination if they were published under free access through the digital library of the University of Brescia (Italy), and provided full text. Articles were excluded if the topic was beyond the aim of our study. Finally, we selected 15 articles. Results We describe a case of KS in COVID-19 patient and postulate that Interleukin-6 (IL-6) activity and steroid-induced immunodeficiency may play a major role in KS emergence. No published case of disseminated KS following COVID-19 in otherwise healthy individuals was found through the systematic literature review, despite the high incidence of COVID-19 in areas with medium–high prevalence of HHV-8 infection. This observation might be explained by the role of individual genetic susceptibility factors. Conclusions SARS-CoV-2 infection and its treatment may lead to reactivation of several latent infections, including HHV-8 and its related clinical syndrome, Kaposi sarcoma.